The neural correlates of interference control dysfunction of working memory in major depressive disorder: An event-related potential study - Jin, Sha-yu; Zhang, Jia-zhao; Sun, Ru-hong; Jiang, Chen-guang; Wang, Jun; Zhou, Zhen-he (Frontiers in Psychiatry, 2022)
Interference control function is a key factor in a series of specific functions of working memory (WM), which is usually impaired in patients with major depressive disorder (MDD). Event-related potentials (ERPs) have advantages to explore the neural processing of interference control and WM impairment, and therefore it is of help to further understand the neural mechanism of MDD. In the present study, 44 patients with MDD and 44 age- and sex-matched healthy controls (HC) were recruited. All participants completed a 4-gradient difficulty Brown-Peterson task (BPT), whose difficulty was manipulated by changing the demand of interspersed distraction tasks. High-density EEG was simultaneously recorded. Hit rate and reaction time (RT) towards target stimulus as well as the underlying ERP features were analyzed. Results showed that when compared with HCs, MDD patients had significantly lower hit rates and longer RTs among all four difficulties of BPT. As for ERP components, no significant between-group difference was found in both N100 and P200 average amplitudes; however, different from the relative stable pattern in the HC group, the centroparietal late positive potential (LPP) amplitude of MDD group decreased with the increase of BPT difficulty, while in high-order difficult BPT tasks, the LPP amplitude of MDD group was significantly smaller than that of HC group. Our findings suggest that failure to control interference well may play a critical role in the impairment of WM in patients with MDD, and provided new evidence that the neural correlates of interference control dysfunction of WM in MDD.